Demonstration Of Supplementary Food Preparation Using Tempe and Moringa Pudding - Rizki Eka Sakti Octaviani; Dhian Fitri Anggraini; Dinaryati Mawardani. T (UKInstitute, 2026)
Nutritional problems are still the main health issue in Indonesia, including in Labibia Village, Mandonga District, Kendari City. Cases of Chronic Energy Deficiency (KEK) in pregnant women and toddlers T in toddlers show the need for community-based nutrition interventions. One of the efforts made is through a demonstration of making Supplementary Feeding (PMT) made from local ingredients